2020
DOI: 10.5817/cp2020-1-2
|View full text |Cite
|
Sign up to set email alerts
|

When you think you know: The effectiveness of restrictive mediation on parental awareness of cyberbullying experiences among children and adolescents

Abstract: The current study examined parental awareness of their child’s cyberbullying experiences in relation to the implementation of restrictive mediation strategies (e.g., interaction and technical restrictions) among children in elementary school and adolescents in high school. Canadian parent-child dyads (N = 102) completed a survey where parents reported their perceptions of their child or adolescent’s involvement in cyber aggression, cyber victimization, and witnessing cyber aggression, while children and adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
1
23
2
1
Order By: Relevance
“…It follows that families need to deepen their knowledge about online relationships and the risks they imply, but also to assume their own responsibility to intervene in this area of education. These conclusions are in line with current research that points out the importance for parents to know strategies of positive and safe parental mediation in the digital education of their children [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It follows that families need to deepen their knowledge about online relationships and the risks they imply, but also to assume their own responsibility to intervene in this area of education. These conclusions are in line with current research that points out the importance for parents to know strategies of positive and safe parental mediation in the digital education of their children [31].…”
Section: Discussionsupporting
confidence: 90%
“…It is known that family beliefs play an important role in the education of children in general and in the management of skills to prevent cyberbullying [ 29 ]. Parental knowledge and awareness are the first step towards prevention and intervention for children who are cyberbullies or cybervictims, as well as for those who witness cyberbullying [ 31 ]. So far, there is limited research that has examined parents′ awareness of their children′s online behaviour, especially in relation to exposure to cyberbullying.…”
Section: Introductionmentioning
confidence: 99%
“…When minors are around 16 years old, parents lower their level of mediation despite the high vulnerability of girls on social networks such as YouTube (García-Jiménez et al 2022). Parents continue to exercise active mediation and dialogue, but they reduce their intervention and they do not advocate the restrictive mediation mentioned by Caivano et al (2020). This decrease in parental involvement might be due to three main causes: (1) they believe their children have greater digital competency as they grow older, (2) they are not aware of the relevance of this period in the growth of minors, and (3) when minors reach adolescence, they demand greater freedom and trust from their parents.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, many parents in our study were not aware of their children's online behaviors or activities. As a result, more parental education is needed to increase awareness around internet safety issues and to demonstrate appropriate monitoring and restrictive mediation strategies (Caivano et al, 2020). American School Counselor Association (2019) also indicated that school counselors can provide parent workshops as an indirect student service.…”
Section: Discussionmentioning
confidence: 99%